Применение метода Лагранжа-Ритца-Канторовича к анализу колебаний турбинных лопаток - Елисеев, Владимир Васильевич; Москалец, Артем Анатольевич (НТУ "ХПИ", 2016)
Рассматриваются колебания турбинных лопаток как линейно упругих естественно закрученных консольных прямых стержней. Прогибы аппроксимируются по методу Ритца. Коэффициенты аппроксимации являются функциями времени согласно Канторовичу. Для их определения составлены уравнения Лагранжа, решаемые численно средствами системы компьютерной математики (MathCAD). Методика позволяет проводить полный модальный анализ, а также рассчитывать нестационарные свободные и вынужденные колебания. Представлены результаты расчета для лопатки паровой турбины Калужского турбинного завода.

The purpose of this effort is the method of vibration analysis. Object of research is turbine blade. A calculation method based on Lagrange equations is proposed. Blade is assumed to be an elastic rectilinear twisted rod. Linear theory is used which means that translational and angular displacements, as well as the loads, are supposed to be small. Deflections are approximated using the method of Ritz. The coordinate functions correspond to the boundary conditions. The coefficients of approximation are time dependent parameters according to the method of Kantorovich. These coefficients are generalized coordinates. Lagrange equations are solved numerically by means of computer mathematics system (MathCAD). This method enables us to calculate natural frequencies and modes of blade and analyze unsteady free vibrations and forced ones.
Application of the Lagrange-Ritz-Kantorovich method to the vibration analysis of turbine blades
Keywords: естественно-закрученные стержни; линейная теория стержней; уравнения Лагранжа; компьютерная математика; twisted rods; Lagrange equations; computer mathematics